Note on the Occurrence of Wendlandia speciosa Cowan (Rubiaceae) in India - Naithani, H. B. (Indian Forester, 1986)
Wendlandia speciosa Cowan- a rare taxon known from Upper Burma, China and Bhutan is now reported from Arunachal Pradesh India. In view of its large fragrant flowers its gardening interest is emphasized.